Moustérienska »koščena piščal« in druge najdbe iz Divjih bab I v Sloveniji = Mousterian "Bone Flute" and Other Finds from Divje Babe I Cave Site in Slovenia - Turk, Ivan (Opera Instituti Archaeologici Sloveniae, 1997)
The most topical Middle Paleolithic site in Slovenia is presented in full and discussed in detail in this series. The Divje Babe I cave site became famous for the archaeological discovery of what current investigations indicate could be the oldest flute, made of the bone of a cave bear, yet discovered. The principal part of the compilation is dedicated to a typological, technological, acoustic and musicological discussion of the remarkable find. Individual chapters present the stratigraphy, chronology, fauna and flora from the site, in addition to the Paleolithic material finds (however, only up to the layer including the bone flute). The book incorporates the first abridged and summarized determinations from the current archaeological excavations, which are not yet concluded. In addition to the editor, who is also the author and coauthor of the majority of chapters, the following individuals also provided contributions to the series: G. Bastiani, M. Culiberg, J. Dirjec, B. Kavur, B. Kryštufek, T.-L. Ku, D. Kunej, D. E. Nelson, M. Omrzel-Terlep and A. Šercelj.